Analysis of the distribution characteristics and influencing factors of geological hazards in Zhejiang Province based on fractal theory - Menglan DAI; Zhibo CHEN; Guodong SHI (Zhongguo dizhi zaihai yu fangzhi xuebao, 2022)
The multifractal method is introduced in the study of the spatial distribution characteristics of geological hazards in Zhejiang Province, and the influencing factors of geological hazards distribution are studied based on the fractal theory. The research results show that the spatial distribution of geological hazards in Zhejiang Province has obvious fractal characteristics, and the northwest and southeast regions are more developed; The terrain is related to the topography. Among them, within the range of rainfall of 2232−2565 mm, the slope of 25°−35°, the slope of 500−1000 m, and Jurassic strata, collapse, landslide, and debris flow are obviously developed. Internal geological hazards are prone to occur. In the distribution of roads in Zhejiang Province, the distribution of provincial roads has a greater impact on the development of geological hazards; the Qiantang River and Oujiang River systems in Zhejiang Province are more complex and have a greater impact on the development of geological hazards. The research results further clarified the distribution characteristics of geological hazards in Zhejiang Province and the influence laws of main influencing factors, which have guiding and reference significance for disaster prevention and control.